Engagement in business simulation games: A self‐system model of motivational development. (18th March 2019) - Buil, Isabel; Catalán, Sara; Martínez, Eva
Abstract: This research draws on the self‐system model of motivational development to explain how the use of business simulation games in class facilitates students' engagement and enhances their learning. Based on a survey of 360 undergraduate students who played a business simulation game in a marketing course, the findings show that students' perceptions of competence, autonomy, relatedness and self‐efficacy have a positive impact on their cognitive, emotional and behavioural engagement. In addition, cognitive and emotional engagement have a positive influence on skills development and perceived learning.